Combined Use of Delamanid and Bedaquiline to Treat Multidrug-Resistant and Extensively Drug-Resistant Tuberculosis: A Systematic Review - Migliori, Giovanni; Pontali, Emanuele; Sotgiu, Giovanni; Centis, Rosella; D’Ambrosio, Lia; Tiberi, Simon; Tadolini, Marina; Esposito, Susanna (International journal of molecular sciences, 2017)
The new drugs delamanid and bedaquiline are increasingly being used to treat multidrug-resistant (MDR-) and extensively drug-resistant tuberculosis (XDR-TB). The World Health Organization, based on lack of evidence, recommends their use under specific conditions and not in combination. No systematic review has yet evaluated the efficacy, safety, and tolerability of delamanid and bedaquiline used in combination. A search of peer-reviewed, scientific evidence was carried out, aimed at evaluating the efficacy/effectiveness, safety, and tolerability of delamanid and bedaquiline-containing regimens in individuals with pulmonary/extrapulmonary disease, which were bacteriologically confirmed as M/XDR-TB. We used PubMed to identify any relevant manuscripts in English up to the 23 December 2016, excluding editorials and reviews. Three out of 75 manuscripts retrieved satisfied the inclusion criteria, whilst 72 were excluded for dealing with only one drug (three studies), being recommendations (one study) or identifying need for their use (one study), focusing on drug resistance aspects (six studies) or being generic reviews/other studies (61 papers). The studies retrieved reported two XDR-TB cases observed for six months and achieving consistent sputum smear and culture conversion. Case 2 experienced a short break of bedaquiline, which was re-started after introducing verapamil. After a transient and symptom-free increase of the QT interval from week 5 to 17, it then decreased below the 500 ms threshold.